Unexpected microanatomical variation among Eocene Antarctic stem penguins (Aves: Sphenisciformes) - Cerda, Ignacio Alejandro; Tambussi, Claudia Patricia; Degrange, Federico Javier (Historical Biology)
The microanatomical and histological structure of Eocene Antarctic stem penguin tarsometatarsi is examined in order to characterise the bone microstructure. Eight adult tarsometatarsi belonging to eight fossil species (Palaeeudyptes gunnari, Palaeeudyptes klekowskii, Anthropornis grandis, Anthropornis nordenskjoeldi, Archaeospheniscus wimani, Marambiornis exilis, Delphinornis arctowskii and Delphinornis larseni) collected from the Antarctic A. nordenskjoeldi Biozone (La Meseta Formation, ,34.2 Ma) were examined. The thin sections revealed a distinctive microanatomical variation among taxa. Whereas Anthropornis spp., A. wimani and P. gunnari possess massive, clearly osteosclerotic bones (medullary cavities absent or strongly reduced), the bones of Delphinornis spp., P. klekowski and M. exilis exhibit well-developed medullary cavities. The cortical bone in all the specimens consists of primary, well-vascularised fibro-lamellar bone and variable amounts of secondary bone. Medullary cavities are coated by a thick layer of lamellar bone tissue and coarse compacted cancellous bone. Although several causes can explain the striking microanatomical variation (e.g. ontogeny), we interpret that such variation is related to differential adaptations to the aquatic life, for which taxa with more massive bones were possibly adapted to deeper and more prolonged diving excursions. Fil: Cerda, Ignacio Alejandro. Universidad Nacional de Río Negro; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: Tambussi, Claudia Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Degrange, Federico Javier. Consejo Nacional de ...